A Young Man's Passage - Clary, Julian (London Ebury Press, 2005)
A long way from the usual ghosted celebrity autobiography, this is Julian Clary's debut as a writer of huge talent - perhaps closer in style to Fay Weldon or Muriel Spark than Dale Winton. Julian has led a unique life. From boarding school, where unholy monks taught him the rudiments of glamour, alternative living and brutality, through to art school in London while the punk and alternative comedy revolution was in full swing, finding out by practical trial and error whether he was gay or straight, his huge success and fame as probably the most high profile gay man in the country and, during the same period, the pain of losing those close to him and the high price of his fame. This is the first time he has voiced his private life and he will bring to its telling all the elegance, economy and integrity that have always informed his comedy. And, possibly, the odd double entendre.
Include Illustration
Keywords: Clary, Julian -- Gay Men -- Comedians